Comparison of the performances of the ADXBLADDER test and urinary cytology in the follow‐up of non‐muscle‐invasive bladder cancer: a blinded prospective multicentric study. (29th August 2020) - Gontero, Paulo; Montanari, Emanuele; Roupret, Morgan; Longo, Fabrizio; Stockley, Jacqueline; Kennedy, Ashleigh; Rodriguez, Oscar; McCracken, Stuart R.C.; Dudderidge, Tim; Sieverink, Caroline; Vanié, Felicien; Allasia, Marco; et al.
Abstract : Objective: To compare directly the performance of the ADXBLADDER test with that of cytology in the detection of non‐muscle‐invasive bladder cancer (NMIBC) recurrences. Background: ADXBLADDER is a urine test based on the detection of MCM5, a DNA licensing factor expressed in all cells capable of dividing. Expression is usually restricted to the basal stem cell compartment; however, in malignancy, MCM5‐expressing cells can be found throughout the epithelium. Detection of MCM5 in urine sediment can be indicative of the presence of a bladder tumour. Patients and Methods: A multicentre prospective, blinded study was carried out from August 2017 and July 2019 at 21 European Union centres, 14 of which collected matching cytology data. Urine was collected from patients prior to cystoscopy. Urine cytology and ADXBLADDER were performed and compared to the diagnosis obtained by cystoscopy. The performance of cytology and ADXBLADDER were then compared. Results: The overall performance of ADXBLADDER demonstrated a sensitivity of 51.9%, a specificity of 66.4%, and a negative predictive value (NPV) of 92%. The sensitivity of ADXBLADDER for low‐ and high‐grade recurrences was 44.1% and 58.8%, respectively. By contrast, cytology sensitivity was 16.7%, specificity was 98% and NPV was 90.7%. Cytology sensitivity for both low‐ and high‐grade disease was 17.6%. Conclusions: ADXBLADDER detection of both low‐ and high‐grade NMIBC recurrence is superior to that of cytology, with ADXBLADDER able to exclude the presence of high‐grade recurrence in 97.8% of cases compared to 97.1% with cytology. These results show that ADXBLADDER has promise as a more reliable alternative to urine cytology in the follow‐up of NMIBC.